The Influence of Saturday Clean Program on the Formation of Environmental Care Character of Elementary School Students - Putra, Rizqi Fajar Adi; Ramadan, Zaka Hadikusuma (Jurnal Kiprah Pendidikan, 2025)
This study aims to determine the effect of the Clean Saturday Program on the formation of environmental awareness among students. The background of this study stems from the low awareness of students regarding school environmental cleanliness, such as littering, not performing cleaning duties, and lacking participation in community service activities. The Clean Saturday Program is a weekly routine activity involving the entire school community in maintaining environmental cleanliness, with the hope of fostering an environmentally conscious attitude among students. This study employs a quantitative approach using a correlational survey method. The study population consists of 190 students, with a sample of 66 students selected using proportional random sampling. The research instrument was a questionnaire that was tested on 30 non-sample respondent, to ensure its validity and reliability. After being declared valid, the questionnaire was distributed to the main sample. The results of the data analysis showed a significant influence between the implementation of the Clean Saturday Program and the formation of students' environmental awareness. This is evidenced by the results of the simple linear regression test, which yielded a significance value less than 0.05 and a coefficient of determination value indicating the program's contribution to students' character. It can be concluded that the Clean Saturday Program has a positive influence on the formation of students' environmental awareness character. Therefore, this program should be continued and developed to be more effective and have a broader impact